Epidemiology of Shiga toxin-producing Escherichia coli in commericial feedlot cattle - Cull, Charley Abraham (Kansas State University, 2016)
Shiga toxin-producing Escherichia coli serogroups (O26, O45, O103, O111, O121, O145, and O157; STEC-7) are recognized as major food-borne pathogens with outbreaks, human infections, and occasional deaths associated with the consumption of contaminated foods. Cattle are recognized as the primary reservoir for STEC-7 and shed these bacteria in their feces, which are considered a principal source of contamination of cattle hides and carcasses at harvest. Pre-harvest interventions that effectively reduce fecal shedding of STEC-7 have the potential to reduce the public health concerns and economic impact of these bacteria and enhance food safety. In the research presented in this dissertation, distinct study designs were used to evaluate the impact of commercially available pre-harvest interventions and develop a better understanding of the epidemiology of STEC-7 in commercial feedlot cattle. A randomized pen-level trial indicated that a commercially available vaccine significantly reduced the fecal prevalence of STEC O157 and prevalence of high shedders compared to unvaccinated pens. However, there was no evidence of a direct-fed microbial (DFM) effect on either measure of STEC O157 shedding. In a continuum of the efficacy study, the performance and carcass characteristics associated with these pre-harvest interventions were quantified. Results indicated that feeding the DFM to cattle improved performance, whereas the vaccine negatively impacted performance during the intervention period, though most of these attributes were not reflected at the time the animals were harvested. Later, a cross-sectional observational study was used to determine the regional-, feedlot- and pen-level fecal prevalence of enterohemorrhagic Escherichia coli (EHEC), a subset of STEC, in commercial feedlot cattle. Results indicated that EHEC serogroup O157 was detected more frequently than non-O157 serogroups of EHEC; however, all feedlots had at least one sample positive for both O157 and non-O157 EHEC. Further, risk factors associated with non-O157 serogroups of EHEC were identified; further evaluation of these factors as potential control points may enable the ability to positively impact public health concerns and food safety by reducing the pathogen load prior to harvest. Overall, the research described in this dissertation provides an assessment of pre-harvest interventions and multi-level prevalence estimates of STEC-7 in commercial feedlot operations.
Keywords: Cattle; E. coli; Feedlot; Performance; STECFood safety